Development and Validation of Rp-Hplc Method For Simultaneous Estimation of Dapagliflozin and Metoprolol In Synthetic Mixtures: Stability Indicating Study (International Journal of Food and Nutritional Sciences, 2023)
Background: The invention of a composition combining beta-blockers and an SGLT2 inhibitor aims to treat heart failure with reduced ejection fraction (HfrEF), whether accompanied by type-2 diabetes or not. Objective: This study aimed to develop a straightforward, precise, accurate, and reproducible stability assay method for quantifying dapagliflozin and metoprolol in a synthetic mixture using RP-HPLC. Method: Separation was achieved using a Waters HPLC system with an Ultrasphere C18 column (250×4.6 mm, 5 µm), employing a mobile phase of Methanol : ACN : Phosphate Buffer pH 3.0 (60:10:30) adjusted with orthophosphoric acid. The flow rate was set at 0.8 ml/min, and detection was at 223 nm. Result: The developed method was successfully applied for quantification and validation of the drugs according to ICH guidelines. The retention times for dapagliflozin and metoprolol were 7.012 and 3.392 minutes, respectively. The linearity ranges were 1-50 µg/mL for dapagliflozin and 5-250 µg/mL for metoprolol. Limits of detection (LOD) and quantification (LOQ) were found to be 0.15 and 0.46 µg/mL for dapagliflozin, and 0.13 and 0.40 µg/mL for metoprolol. The method exhibited % recoveries within acceptable limits across 50%, 100%, and 150% of the working concentration levels. Stability studies subjected the drug to conditions including acid, base, oxidation, thermal, and photolytic stress, per ICH guidelines. Conclusion: The results demonstrate that the developed analytical method is suitable for its intended purpose, meeting the criteria defined in ICH Q2R2 guidelines.